A new species and new records of Lecanora (Lecanoraceae, lichenized Ascomycota) with usnic acid from the Antarctic region - Rosa, Iris Nadia De La; Passo, Alfredo; Rodríguez, Juan Manuel; Chiapella, Jorge Oscar; Messuti, María Inés (Phytotaxa, 2016)
A new species of Lecanora, L. flavocrassa, is described from the Antarctic region. Additionally, L. stenotropa is registered for the first time from Antarctica and the distribution range of L. intricata is extended to the Antarctic Peninsula. A key to the species of Lecanora from Antarctica that contain usnic acid as secondary metabolite is presented.